How Does Problem-solving Method Affect Students’ Self-confidence and Mathematical Understanding? - Rahayuningdewi, Putri Dorojatun; Faradillah, Ayu (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aimed to determine the effects of problem-solving method on students’ self-confidence and mathematical understanding in learning. This study used quantitative and qualitative methods. The research followed the process of quantitative calculation from instruments about mathematical understanding and described students’ self-confidence, analyzed using Rasch with the WinSteps application. This research was conducted at SMPN 30 Jakarta with class VIII students as the research population. Based on this population, 34 students were selected as the sample with a cluster random sampling technique. Based on the data obtained, it was known that there is a significant effect of problem-solving methods on mathematical understanding. Meanwhile, Rasch data analysis showed a high category for the relationship between understanding and self-confidence of students by 60%. This proved that the effect of the problem-solving method on self-confidence and mathematical understanding is directly proportional.